2007
DOI: 10.1002/bmb.1
|View full text |Cite
|
Sign up to set email alerts
|

Learning in a gene technology laboratory with educational focus: Results of a teaching unit with authentic experiments

Abstract: In an effort to overcome deficiencies in teaching molecular biology at school, a workshop in an out-ofschool laboratory including only authentic experiments was developed. Evaluation of 337 A-level 12th graders followed a quasi-experimental design, with one hands-on group, two non-experimental control groups (at school/in the laboratory), and one group with no intervention. Their cognitive achievement was monitored by pre-, post-, and retention tests and analyzed for inter-group differences. Test items were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
3
36
1
1
Order By: Relevance
“…Instead of simply offering a traditional lecture-based course to address this, we felt a more effective route would be to provide students with a hands-on opportunity to participate in bioinformatics research [2][3][4]. Hands-on learning strategies primarily follow three different models.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of simply offering a traditional lecture-based course to address this, we felt a more effective route would be to provide students with a hands-on opportunity to participate in bioinformatics research [2][3][4]. Hands-on learning strategies primarily follow three different models.…”
Section: Introductionmentioning
confidence: 99%
“…We took the sum-scores of KT1 (pretest; applied one week before the lesson) as indicators of students' previous knowledge. A weighted difference between sum-scores of KT2/3 and KT1 (Scharfenberg, Bogner, & Klautke, 2007) yielded short-term/long-term cognitive achievement scores. For instance, we calculated long-term cognitive achievement scores as follows:…”
Section: Knowledge Tests As Instrument To Value Effectiveness Of the mentioning
confidence: 99%
“…Our own research has shown that students often have very little experience in independently conducting experiments at school (7). One potential cause may be resource limitations due to financial restrictions.…”
Section: Introductionmentioning
confidence: 99%